Interoceptive Axes Dissociation in Anorexia Nervosa: A Single Case Study With Follow Up Post-recovery Assessment - Di Lernia, Daniele; Serino, Silvia; Polli, Nicoletta; Cacciatore, Chiara; Persani, Luca; Riva, Giuseppe (Frontiers in Psychology, 2019)
Anorexia nervosa (AN) is a disorder characterized by alterations in body perception. Recent literature suggested that AN can also impair the processing of stimuli from inside the body (i.e. interoceptive). Considering the role of interoceptive signals in self-perception and body awareness, the study presented the case of Diana, a 25 years old woman affected by AN. The case study described an interesting and unique clinical pattern with a severe dissociation between interoceptive perceptions that nonetheless appeared restored after the subject’s clinical recovery. At hospital admission (BMI = 16.06 kg/m2), Diana performed a complete interoceptive assessment for accuracy (IAc), metacognitive awareness (IAw), sensibility (IAs), and interoceptive buffer saturation (IBs) – a new index that behaviourally evaluated the amount of interoceptive processing. Measures were repeated after an outpatients rehabilitative hospital recovery program (BMI = 19.00 kg/m2). Results were confronted with a control (N=4) of healthy female subjects. Analyses indicated severe deficits in accuracy (IAc), buffer saturation (IBs) and sensibility (IAs) compared to control group. Conversely, metacognitive awareness (IAw) was pathologically enhanced. After the rehabilitative hospital program, Diana’s interoceptive patterns appeared completely restored, with no difference in interoceptive variables compared to the control group. Interestingly, IAs showed that Diana perceived her body even less safe and trustworthy than before. In conclusion, this case illustrated a very specific dissociation between interoceptive axes in AN, whereas deeply pervasive deficits in perception and processing were accompanied by a pathologically enhanced confidence in the wrong perceptions. An effective rehabilitative program was able to improve Diana’s clinical condition, also restoring the interoceptive alterations. Nonetheless, Diana’s cognitive beliefs appeared disrupted, suggesting a profound positive shift in her cognitive awareness and the psychological need to accommodate a new body perspective.